ENGLISH VOWELS PRONUNCIATION ACCURACY: AN ACOUSTIC PHONETICS STUDY WITH PRAAT - Widya Widya; Erika Agustiana (Scope : Journal of English Language Teaching, 2020)
Analyzing speech production acoustically by using PRAAT software and by taking minimal pairs as research data will help us to examine pronunciation accuracy. The causes of mistake and the factors affecting pronunciation phonetically may be detected through this analysis. This study aimed to measure the accuracy of the pronunciation of English vowel sounds by third-semester students majoring in English Education by comparing them to the standard pronunciation by a native speaker of English and to find factors causing pronunciation problems. This descriptive qualitative research was conducted by following the research phases, that is, (1) data collection, (2) data analysis, and (3) presentation of the result. The results show that, out of four participants, there was only one participant who can distinguish front and back vowels correctly while the other three participants failed to do so at certain vowel sounds. The most common mistake was at long and short vowels ([i:] : [I] and [u:] : [?]). Participants failed to distinguish long and short vowels even though they have been informed that they are different. Furthermore, the problems of pronouncing [æ], [?:], and [?] varied across the participants. The first language interference, attitude toward English, and lack of motivation are indicated to be the factors affecting pronunciation. Keywords: Acoustic phonetics; vowels; pronunciation; PRAAT; formant frequency ABSTRAKMenganalisis produksi suara dengan menggunakan perangkat lunak PRAAT dan dengan mengambil pasangan minimal sebagai data penelitian akan membantu kita untuk memeriksa keakuratan pelafalan. Penyebab kesalahan dan faktor-faktor yang mempengaruhi pelafalan secara fonetis dapat dideteksi melalui analisis ini. Penelitian ini bertujuan untuk mengukur keakuratan pelafalan bunyi vokal bahasa Inggris oleh mahasiswa semester tiga jurusan Pendidikan Bahasa Inggris dengan membandingkannya dengan pengucapan standar oleh penutur asli bahasa Inggris dan untuk menemukan faktor-faktor yang menyebabkan masalah pelafalan. Penelitian kualitatif deskriptif ini dilakukan dengan mengikuti tahapan penelitian, yaitu (1) pengumpulan data, (2) analisis data, dan (3) penyajian hasil. Hasil menunjukkan bahwa, dari empat pertisipan, hanya ada satu partisipan yang dapat membedakan bunyi vokal depan dan belakang dengan benar sedangkan tiga peserta lainnya gagal melakukannya pada bunyi vokal tertentu. Kesalahan paling umum adalah vokal panjang dan pendek ([i:]: [I] dan [u:]: [?]). Peserta gagal membedakan vokal panjang dan pendek meskipun mereka telah diberitahu bahwa bunyi-bunyi itu berbeda. Lebih lanjut, masalah pelafalan [æ], [?:], dan [?] bervariasi antar peserta. Gangguan bahasa pertama, sikap terhadap bahasa Inggris, dan kurangnya motivasi diindikasikan sebagai faktor yang mempengaruhi pelafalan. Kata kunci: fonetik akustik; bunyi vokal; pelafalan; PRAAT; frekuensi forman